Negative electrode material, preparation method thereof and battery
By introducing interlaced carbon nanotube structure and plasma modification treatment into hard carbon materials, the problem of reducing the first effect of hard carbon materials when increasing sodium storage capacity is solved, and high capacity, high first efficiency and excellent rate performance are achieved. Negative electrode material.
Patent Information
- Application Number
- CN202411252056.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-27
AI Technical Summary
When existing hard carbon materials increase the sodium storage capacity, oxidation and activation will lead to a decrease in the compaction density of the material and a decrease in the first effect, making it difficult to have both high capacity and high first effect.
Using a negative electrode material that combines carbon matrix and carbon nanotubes, the carbon nanotubes are interspersed inside the carbon matrix to form a supporting structure. The structural stability and conductivity of the material are improved through heat treatment and plasma modification treatment, and combined with carbonization treatment, an efficient negative electrode material is formed.
The high sodium storage capacity, excellent rate performance and high first-term efficiency of the negative electrode material are achieved, the compaction density is controlled above 1.3g/cm3, the first Coulomb efficiency reaches more than 93%, and the slope area capacity reaches 150mAh/g.
Smart Images

Figure CN119208553A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of negative electrode materials, and in particular, to negative electrode materials and preparation methods thereof, and batteries. Background Art
[0002] Hard carbon materials have high sodium storage specific capacity, low sodium storage potential, and excellent cycle stability, and are the most promising negative electrode materials for sodium ion batteries. Existing hard carbon materials have the problems of low capacity and poor first efficiency. Although the sodium storage capacity of hard carbon can be increased by oxidation, activation and other methods, oxidation and activation will etch a large number of holes inside the hard carbon. The increase in holes will inevitably lead to a sharp drop in the compaction density of the material, a decrease in the first efficiency of the sodium ion battery, and a decrease in the energy density of the sodium ion battery material. Therefore, how to make the negative electrode material have both high capacity and high first efficiency is a problem that needs to be solved urgently. Summary of the invention
[0003] The present application proposes a negative electrode material and a preparation method thereof, and a battery. The negative electrode material can have high capacity, high initial efficiency and high conductivity.
[0004] In a first aspect, the present application provides a negative electrode material, the negative electrode material comprising a carbon matrix and carbon nanotubes, at least part of the carbon nanotubes being interspersed within the carbon matrix to form a support structure;
[0005] The compaction density of the negative electrode material under 5T pressure is ≥1.3g / cm 3 The powder conductivity of the negative electrode material under a pressure of 20KN is 9.0×10 3 S / m~4.0×10 4 S / m;
[0006] The button-type battery assembled from the negative electrode material has a sodium embedding capacity of ≥150 mAh / g in the slope region of a voltage range above 0.1 V.
[0007] In some embodiments, the carbon nanotubes D / I G ≤0.5.
[0008] In some embodiments, the carbon matrix I D / I G ≥1.3.
[0009] In some embodiments, the carbon nanotubes include at least one of oligo-walled carbon nanotubes, single-walled carbon nanotubes, and multi-walled carbon nanotubes.
[0010] In some embodiments, the outer diameter of the carbon nanotubes is 0.3 nm to 20 nm.
[0011] In some embodiments, the average length of the carbon nanotubes is 10 nm to 10 μm.
[0012] In some embodiments, the interlayer spacing of the carbon matrix is
[0013] In some embodiments, the volume median particle size D50 of the negative electrode material is 3 μm to 30 μm.
[0014] In some embodiments, the particle size distribution index of the negative electrode material satisfies: 1.4≤(D 90 -D 10 ) / D 50 ≤1.6.
[0015] In some embodiments, the ash content of the negative electrode material is 0.005% to 0.05% based on the mass of the negative electrode material.
[0016] In some embodiments, based on the mass of the negative electrode material, the mass content of calcium and / or magnesium in the negative electrode material is less than 6 ppm.
[0017] In some embodiments, based on the mass of the negative electrode material, the mass content of iron and / or nickel in the negative electrode material is less than 3 ppm.
[0018] In some embodiments, the button-type battery assembled from the negative electrode material has an initial coulombic efficiency of ≥93%, and a reversible charge specific capacity of ≥360 mAh / g.
[0019] In a second aspect, the present application provides a method for preparing a negative electrode material, the method comprising the following steps:
[0020] A mixture including a resin-based carbon source material and carbon nanotubes containing functional groups is heat-treated and crushed to obtain a precursor; wherein the functional groups include at least one of hydroxyl, carboxyl, ether, amino and metal ions;
[0021] Using a plasma-treated reducing gas flow to modify the surface of the precursor to obtain a composite;
[0022] The composite is carbonized to obtain a negative electrode material.
[0023] In some embodiments, the resin-based carbon source material includes at least one of a thermosetting resin and a thermoplastic resin.
[0024] In some embodiments, the resin-based carbon source material includes at least one of epoxy resin, phenolic resin, polyvinyl chloride resin, and polyurethane.
[0025] In some embodiments, the mass ratio of the resin-based carbon source material to the carbon nanotubes containing functional groups is (10-10000):1.
[0026] In some embodiments, the heat treatment is performed at a temperature of 80°C to 200°C.
[0027] In some embodiments, the heat treatment time is 10 min to 600 min.
[0028] In some embodiments, the ash content of the precursor is ≤0.5% based on the mass of the precursor.
[0029] In some embodiments, the heat treatment is performed under a protective atmosphere comprising at least one of nitrogen, argon, helium, carbon monoxide, carbon dioxide, air, and oxygen.
[0030] In some embodiments, the carbon nanotubes containing functional groups include at least one of oligo-walled carbon nanotubes, single-walled carbon nanotubes, and multi-walled carbon nanotubes.
[0031] In some embodiments, the volume median particle size D50 of the precursor is 3 μm to 30 μm.
[0032] In some embodiments, the reducing gas stream comprises a reducing gas comprising at least one of carbon monoxide, hydrogen, hydrogen sulfide, methane, chlorine, and sulfur monoxide.
[0033] In some embodiments, the reducing gas flow further includes a carrier gas, and the carrier gas includes at least one of nitrogen, argon, helium, and carbon dioxide.
[0034] In some embodiments, the reducing gas flow further includes a carrier gas and a reducing gas, and the volume ratio of the reducing gas to the carrier gas is 1:(1-100).
[0035] In some embodiments, the modification treatment includes a first stage and a second stage, the temperature of the first stage is 20°C to 40°C, and the treatment time of the first stage is 10min to 120min; the temperature of the second stage is 700°C to 800°C, and the treatment time of the second stage is 10min to 300min.
[0036] In some embodiments, the temperature of the carbonization treatment is 1000°C to 1400°C.
[0037] In some embodiments, the carbonization treatment time is 0.5h to 4h.
[0038] In some embodiments, the carbonization treatment is performed under a protective atmosphere, and the protective atmosphere includes at least one of helium, neon, argon, nitrogen, krypton and xenon.
[0039] In a third aspect, the present application provides a battery, comprising the above-mentioned negative electrode material or a negative electrode material prepared by the above-mentioned method for preparing the negative electrode material.
[0040] Compared with the prior art, the technical solution of the present application has the following beneficial effects:
[0041] The negative electrode material provided by the present application includes a carbon matrix and carbon nanotubes. Some carbon nanotubes are interspersed in the interior of the carbon matrix to form a supporting structure, which can improve the structural stability and overall mechanical strength of the negative electrode material. The carbon nanotubes interspersed in the carbon matrix can also increase the interlayer spacing of the carbon matrix, so that the negative electrode material has more ion diffusion paths and more sodium ion storage sites. The good conductivity of carbon nanotubes can facilitate the transmission of ions and electrons, thereby improving the powder conductivity and rate performance of the negative electrode material. At the same time, the compaction density of the negative electrode material is controlled at 1.3g / cm 3 As mentioned above, the negative electrode material has a high compaction density, which can improve the energy density of the negative electrode material, improve the first coulombic efficiency of the negative electrode material, and the slope area capacity of the negative electrode material can reach more than 150 mAh / g. In this application, the negative electrode material can have high sodium storage capacity, high first efficiency and excellent rate performance.
[0042] The preparation method of the negative electrode material provided in the present application uses a resin-based carbon source material as a raw material, and adds carbon nanotubes with functional groups. During the heat treatment process, the carbon nanotubes can quickly react with the active groups in the resin under the auxiliary action of the functional groups to promote the crosslinking of the resin-based carbon source material and enter the resin, thereby realizing the interpenetration of the carbon nanotubes in the resin, and promoting the resin-based carbon source material to complete the transformation from a linear-branched structure to a body-network structure, thereby improving the crosslinking degree of the resin, making the obtained precursor more compact, and the carbon nanotubes are interspersed into the network structure of the resin, which can enhance the stability of the precursor and improve the powder conductivity and rate performance of the precursor. The surface of the precursor is then modified by a plasma-treated reducing airflow, and the reducing airflow can flush the surface of the precursor, greatly reducing the metal heteroatoms in the precursor, such as calcium and magnesium ions. The impact of the reducing airflow after high-temperature energization and the etching of the precursor by the plasma are conducive to removing sp 3 Hybridized carbon to increase carbon nanotube sp 2The proportion of hybrid carbon plays a role in modifying carbon nanotubes, so that the conductivity of carbon nanotubes interspersed on the surface of the resin is further enhanced. Finally, the composite is carbonized, the resin is carbonized to form hard carbon, and the carbon nanotubes form a supporting structure between the layers of hard carbon, which can make the hard carbon have more and richer sodium storage space. The excellent conductivity of carbon nanotubes can also further improve the conductivity of the negative electrode material, so that the rate performance of the negative electrode material is greatly improved, especially the slope area capacity of the negative electrode material is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 A schematic diagram of the structure of the negative electrode material provided in the embodiment of the present application;
[0044] Figure 2 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application;
[0045] Figure 3a and Figure 3b They are respectively SEM images of the negative electrode material provided in Example 1 of the present application at different magnifications;
[0046] Figure 4 A charge and discharge curve diagram of the negative electrode material provided in Example 1 of the present application;
[0047] Figure 5 This is the Raman spectrum of the negative electrode material provided in Example 1 of the present application.
[0048] Description of labels:
[0049] 1-Carbon matrix; 2-Carbon nanotubes. DETAILED DESCRIPTION
[0050] The following is a preferred implementation of the embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the embodiment of the present invention. These improvements and modifications are also considered to be within the scope of protection of the embodiment of the present invention.
[0051] The present application embodiment provides a negative electrode material, such as Figure 1 As shown, the negative electrode material includes a carbon matrix 1 and carbon nanotubes 2, at least part of the carbon nanotubes 2 are inserted into the interior of the carbon matrix 1 to form a support structure;
[0052] Among them, the compaction density of the negative electrode material at 5T pressure is ≥1.3g / cm 3 The powder conductivity of the negative electrode material under a pressure of 20KN is 9.0×10 3 S / m~4.0×10 4 S / m;
[0053] The button cell assembled from the negative electrode material has a sodium embedding capacity of ≥150 mAh / g in the slope region of the voltage range above 0.1 V.
[0054] The negative electrode material provided by the present application includes a carbon matrix and carbon nanotubes. Some carbon nanotubes are interspersed in the interior of the carbon matrix to form a supporting structure, which can improve the structural stability and overall mechanical strength of the negative electrode material. The carbon nanotubes interspersed in the carbon matrix can also increase the interlayer spacing of the carbon matrix, so that the negative electrode material has more ion diffusion paths and more sodium ion storage sites. The good conductivity of carbon nanotubes can facilitate the transmission of ions and electrons, and improve the powder conductivity and rate performance of the negative electrode material. At the same time, the compaction density of the negative electrode material is controlled at 1.3g / cm 3 As mentioned above, the negative electrode material has a high compaction density, which can improve the energy density of the negative electrode material and the first coulombic efficiency of the negative electrode material, so that the slope area capacity of the negative electrode material can reach more than 150 mAh / g. In the present application, the negative electrode material can have high sodium storage capacity, high first efficiency and excellent rate performance.
[0055] In some embodiments, the carbon matrix I D / I G ≥1.3; specifically, it can be 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, etc., and of course, it can also be other values within the above range, which are not limited here. The carbon matrix has a high degree of disorder and a small amount of microcrystalline structure. D / I G Controlling within the above range is beneficial to increasing the storage sites of active ions in the carbon matrix, improving the transport performance of active ions, and increasing the capacity of the negative electrode material.
[0056] In some embodiments, the interlayer spacing of the carbon matrix is Specifically it can be or The interlayer spacing of the carbon matrix is controlled within the above range, which is beneficial to increase the ion diffusion path and sodium ion storage sites inside the negative electrode material and improve the capacity of the negative electrode material.
[0057] In some embodiments, the carbon nanotubes D / I G ≤0.5; specifically, it can be 0.5, 0.48, 0.45, 0.43, 0.41, 0.35, 0.31, 0.3, 0.25, 0.22, etc., and of course, it can also be other values within the above range, which are not limited here. D / I GWhen the content of carbon nanotubes is controlled within the above range, the carbon nanotubes have fewer defects and a higher degree of graphitization, so that the carbon nanotubes have good electrical conductivity.
[0058] In some embodiments, the carbon nanotubes 2 include at least one of oligo-walled carbon nanotubes, single-walled carbon nanotubes, and multi-walled carbon nanotubes.
[0059] In some embodiments, the average length of the carbon nanotubes 2 is 10 nm to 10 μm; specifically, it can be 10 nm, 20 nm, 50 nm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, etc., which is not limited here.
[0060] In some embodiments, the outer diameter of the carbon nanotube 2 is 0.3 nm to 20 nm, and specifically can be 0.3 nm, 1 nm, 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm or 20 nm, etc., which is not limited here.
[0061] In some embodiments, part of the carbon nanotubes are connected to the surface of the carbon matrix, and part of the carbon nanotubes are inserted into the interior of the carbon matrix to form a support structure.
[0062] In some embodiments, the powder conductivity of the negative electrode material under a pressure of 20 KN is 9.0×10 3 S / m~4.0×10 4 S / m, specifically 9.0×10 3 S / m, 9.5×10 3 S / m, 1.0×10 4 S / m, 1.1×10 4 S / m, 1.2×10 4 S / m, 1.5×10 4 S / m, 2.0×10 4 S / m, 2.5×10 4 S / m, 2.8×10 4 S / m, 3.0×10 4 S / m, 3.3×10 4 S / m, 3.5×10 4 S / m, 4.0×10 4 S / m, etc., of course, it can also be other values within the above range, which is not limited here. Preferably, the powder conductivity of the negative electrode material is 1.3×10 4 S / m~4.0×10 4 S / m.
[0063] In some embodiments, the compaction density of the negative electrode material is ≥ 1.3 g / cm 3, specifically 1.4 g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 or 2.1 g / cm 3 Of course, it can also be other values within the above range and is not limited here.
[0064] In some embodiments, the volume median particle size D of the negative electrode material is 50 The particle size of the negative electrode material is 3 μm to 30 μm, and specifically can be 3 μm, 4 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm or 8 μm, etc., and of course can be other values within the above range, which are not limited here. Controlling the particle size of the negative electrode material within the above range is conducive to providing more active sites and improving the cycle performance of the battery made of the negative electrode material.
[0065] In some embodiments, the particle size distribution index of the negative electrode material satisfies: 1.4≤(D 90 -D 10 ) / D 50 ≤1.6. The particle size distribution index of the negative electrode material is controlled within the above range, the gaps between the particles of the negative electrode material are reduced, and the compaction density of the negative electrode material can be further improved.
[0066] In some embodiments, the specific surface area of the negative electrode material is 1.0 m 2 / g to 15.0m 2 / g; specifically 1.0m 2 / g, 2.0m 2 / g, 3.0m 2 / g, 4.0m 2 / g, 5.0m 2 / g, 6.0m 2 / g, 7.0m 2 / g, 8.0m 2 / g, 9.0m 2 / g, 10.0m 2 / g, 12.0m 2 / g or 15.0m 2 / g, etc., and of course, other values within the above range may also be used, which are not limited here. It can be understood that the smaller the specific surface area of the negative electrode material, the better. Too large a specific surface area is likely to cause repeated formation of the SEI film on the surface of the negative electrode material, consume too much irreversible sodium salt, and reduce the initial efficiency of the battery.
[0067] In some embodiments, based on the mass of the negative electrode material, the mass content of calcium and / or magnesium in the negative electrode material is less than 6ppm, specifically 5.9ppm, 5.5ppm, 5.1ppm, 4.9ppm, 4.5ppm, 3.5ppm, 2.9ppm, 2.5ppm, 2.0ppm, 1.5ppm or 1.0ppm, etc., which are not limited here. In the present application, when the negative electrode material contains both calcium and magnesium, the total mass content of calcium and magnesium is less than 6ppm. When the negative electrode material contains calcium or magnesium, the mass content of calcium is less than 6ppm, or the mass content of magnesium is less than 6ppm.
[0068] In some embodiments, based on the mass of the negative electrode material, the mass content of iron and / or nickel in the negative electrode material is less than 3ppm, specifically 2.9ppm, 2.5ppm, 2.0ppm, 1.5ppm or 1.0ppm, etc., which are not limited here. In the present application, when the negative electrode material contains both iron and nickel, the total mass content of iron and nickel is less than 6ppm. When the negative electrode material contains iron or nickel, the mass content of iron is less than 6ppm, or the mass content of nickel is less than 6ppm. In some embodiments, based on the mass of the negative electrode material, the ash content of the negative electrode material is 0.005% to 0.05%, specifically 0.005%, 0.008%, 0.009%, 0.01%, 0.02%, 0.03%, 0.04% or 0.05%, etc., and of course it can also be other values within the above range, which are not limited here.
[0069] In some embodiments, the first coulombic efficiency of a button cell assembled from the negative electrode material is ≥93%.
[0070] In some embodiments, the reversible charge capacity of the button-type battery assembled from the negative electrode material is ≥360 mAh / g.
[0071] The present application also provides a method for preparing a negative electrode active material, the method comprising the following steps S10 to S30:
[0072] S10, heat-treating a mixture of a resin-based carbon source material and carbon nanotubes containing functional groups, and crushing the mixture to obtain a precursor; wherein the functional groups include at least one of hydroxyl, carboxyl, ether, amino and metal ions.
[0073] S20, modifying the surface of the precursor using a plasma-treated reducing gas flow to obtain a composite;
[0074] S30, carbonizing the composite to obtain a negative electrode material.
[0075] The preparation method of the negative electrode material provided by the present application uses a resin-based carbon source material as a raw material, and adds carbon nanotubes with functional groups. During the heat treatment process, the carbon nanotubes can quickly react with the active groups in the resin under the auxiliary action of the functional groups to promote the crosslinking of the resin-based carbon source material and enter the resin, thereby realizing the interpenetration of the carbon nanotubes in the resin, and promoting the resin-based carbon source material to complete the transformation from a linear-branched structure to a body-network structure, thereby improving the crosslinking degree of the resin, making the obtained precursor more compact, and the carbon nanotubes are interspersed into the network structure of the resin, which can enhance the stability of the precursor and improve the powder conductivity and rate performance of the precursor. The surface of the precursor is then modified by a plasma-treated reducing airflow, which can flush the surface of the precursor and greatly reduce the metal heteroatoms in the precursor, such as calcium and magnesium ions. The reducing airflow after high-temperature energization impacts the surface of the precursor, so that the plasma etches the surface of the precursor, which is beneficial to remove sp in the carbon nanotubes. 3 Hybridized carbon to increase carbon nanotube sp 2 The proportion of hybrid carbon plays a role in modifying carbon nanotubes, so that the conductivity of carbon nanotubes interspersed on the surface of the resin is further enhanced. Finally, the composite is carbonized, the resin is carbonized to form hard carbon, and the carbon nanotubes form a supporting structure between the layers of hard carbon, which can make the hard carbon have more abundant sodium storage space. The excellent conductivity of carbon nanotubes can also further improve the conductivity of the negative electrode material, so that the rate performance of the negative electrode material is greatly improved, especially the slope area capacity of the negative electrode material is significantly improved.
[0076] The following is a detailed description of this solution in conjunction with embodiments:
[0077] Step S10, heat-treating a mixture of the resin-based carbon source material and the carbon nanotubes containing functional groups, and crushing the mixture to obtain a precursor.
[0078] In some embodiments, the functional group includes at least one of a hydroxyl group, a carboxyl group, an ether group, an amino group, and a metal ion.
[0079] In some embodiments, the resin-based carbon source material includes at least one of a thermosetting resin and a thermoplastic resin.
[0080] In some embodiments, the resinous carbon source material includes at least one of epoxy resin, phenolic resin, polyvinyl chloride resin, and polyurethane.
[0081] In some embodiments, the mass ratio of the resin-based carbon source material to the carbon nanotubes containing functional groups is (10-10000):1, specifically 10:1, 50:1, 80:1, 100:1, 200:1, 400:1, 500:1, 800:1, 10000:1, etc., which is not limited here.
[0082] It can be understood that the resin-based carbon source material has a -C=O group, and functional groups such as amino and hydroxyl groups can undergo cross-linking reactions with the -C=O group, promoting the transformation of the resin from a linear-branched structure to a body-network structure, increasing the degree of cross-linking of the resin, and making the precursor denser, thereby increasing the compaction density of the obtained negative electrode material, and the overall structural stability of the negative electrode material is also stronger.
[0083] In some embodiments, the carbon nanotubes containing functional groups include at least one of oligo-walled carbon nanotubes, single-walled carbon nanotubes, and multi-walled carbon nanotubes.
[0084] In some embodiments, the resin may be dissolved in a solvent, and then carbon nanotubes may be added and stirred to improve the mixing uniformity of the components. Specifically, the solvent may be an organic solvent such as ethanol or acetone, and the stirring and mixing may be performed in a high-speed disperser.
[0085] In some embodiments, the heat treatment temperature is 80°C to 200°C, specifically 80°C, 90°C, 100°C, 120°C, 150°C, 180°C, 190°C or 200°C, etc., but is not limited to the above.
[0086] In some embodiments, the heat treatment time is 10 min to 600 min, specifically 10 min, 20 min, 30 min, 40 min, 60 min, 120 min, 240 min, 360 min, 420 min or 600 min, etc., but is not limited to the above.
[0087] In the present application, during the low temperature heat treatment of the mixture of resin and carbon nanotubes, the resin is cured and coupled with the carbon nanotubes to form a highly cross-linked three-dimensional network structure. The carbon nanotubes are dispersed in the resin and can act as a conductive bridge, thereby improving the powder conductivity of the negative electrode material.
[0088] In some embodiments, based on the mass of the precursor, the ash content of the precursor is ≤0.5%, and the ash content of the precursor can specifically be 0.5%, 0.4%, 0.3%, 0.2%, 0.1%, 0.05%, etc., but is not limited to the above.
[0089] In some embodiments, the heat treatment is performed under a protective atmosphere comprising at least one of nitrogen, argon, helium, carbon monoxide, carbon dioxide, air, and oxygen.
[0090] In some embodiments, the pulverizing method includes at least one of sand milling, ball milling, ultrasound, and air flow milling.
[0091] In some embodiments, the volume median particle size D50 of the pulverized precursor is 3 μm to 30 μm.
[0092] In some embodiments, the precursor is spherical or spheroidal in shape.
[0093] Step S20, modifying the surface of the precursor using a plasma-treated reducing gas flow to obtain a composite.
[0094] In some embodiments, the plasma may be at least one of microwave plasma, radio frequency plasma, and direct current discharge plasma. The microwave plasma may be formed in a transverse electric field or a transverse magnetic field. The radio frequency plasma mode may be an inductively coupled plasma, a capacitively coupled plasma, and the like.
[0095] In some embodiments, the power of the plasma generating device is 100-800W.
[0096] In some embodiments, the reducing gas stream comprises a reducing gas comprising at least one of carbon monoxide, hydrogen, hydrogen sulfide, methane, chlorine, and sulfur monoxide.
[0097] In some embodiments, the reducing gas flow further includes a carrier gas, and the carrier gas includes at least one of nitrogen, argon, helium, and carbon dioxide.
[0098] In some embodiments, the reducing gas flow also includes a carrier gas and a reducing gas, and the volume ratio of the reducing gas to the carrier gas is 1:(1-100), specifically 1:1, 1:2, 1:5, 1:10, 1:15, 1:20, 1:30, 1:40, 1:50, 1:80 or 1:100, etc., but is not limited to the above.
[0099] In some embodiments, the modification treatment includes a first stage and a second stage, the temperature of the first stage is 20°C to 60°C, and the treatment time of the first stage is 10min to 120min; the temperature of the second stage is 700°C to 800°C, and the treatment time of the second stage is 10min to 300min.
[0100] In some embodiments, the temperature of the first stage can be 20°C, 25°C, 30°C, 35°C, or 40°C, and the processing time of the first stage is 10 min, 20 min, 30 min, 40 min, 60 min, 90 min, 120 min, etc., but is not limited to the above.
[0101] It can be understood that in the first stage, a large amount of plasma flow is generated under the action of the reducing gas, and the plasma flow flushes the precursor. The accelerated plasma flow collides with the precursor frequently, so that the pollutant molecules on the surface of the precursor are decomposed under the impact force of the collision to form small molecular volatiles, which are removed from the surface of the precursor in time with the high-flow gas, which can effectively reduce the content of trace elements such as calcium and magnesium on the surface of the composite, and improve the first-cycle coulomb efficiency of the negative electrode material.
[0102] In some embodiments, the temperature of the second stage can be 700°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, or 800°C, and the processing time of the first stage is 10 min, 20 min, 30 min, 40 min, 60 min, 90 min, 120 min, 240 min, 260 min, or 300 min, etc., but is not limited to the above.
[0103] Understandably, in the second stage, the plasma has a higher activity. At this time, the reducing gas, under the action of the plasma, will etch the amorphous carbon on the surface of the precursor. This etching not only includes a very high proportion of ion sputtering etching but also atomic etching, which significantly improves the etching effect, thereby increasing the degree of defects on the surface of the composite, thereby increasing the sodium embedding space of the carbonized negative electrode material, providing more space for the adsorption and storage of sodium ions, thereby improving the slope area capacity of the negative electrode material and improving the rate performance of the negative electrode material. In addition, high-energy plasma etching can also increase the proportion of sp2 hybridized carbon in carbon nanotubes, play a modifying role, improve the structure of carbon nanotubes, and improve the conductivity of carbon nanotubes, thereby affecting the powder conductivity of the negative electrode material and improving the rate performance of the negative electrode material. High-energy plasma etching can also remove metal impurities in the composite. Since the metal impurities in the composite are impacted and reduced by the reducing gas flow, the metal ions exposed on the surface of the composite are blown out with the carrier gas flow, and the active metal formed by the reduction captures the plasma and is etched again, which gradually reduces the metal impurity content in the composite over and over again, thereby improving the first coulomb efficiency of the negative electrode material, reducing the risk of metal precipitation, and improving the safety performance of the battery.
[0104] Step S30, carbonizing the composite to obtain a negative electrode material.
[0105] In some embodiments, the temperature of the carbonization treatment is 1000° C. to 1400° C., specifically 1000° C., 1100° C., 1150° C., 1160° C., 1180° C., 1200° C., 1250° C., 1300° C., 1350° C. or 1400° C., which is not limited here. It can be understood that during the carbonization process, the resin-based carbon source material in the composite can be fully carbonized under the action of high temperature.
[0106] In some embodiments, the carbonization treatment time is 0.5 h to 4 h, specifically, it can be 0.5 h, 1 h, 2 h, 2.5 h, 3 h, 3.5 h or 4 h, which is not limited herein.
[0107] In some embodiments, the carbonization treatment is carried out under a protective atmosphere, and the protective atmosphere includes at least one of helium, neon, argon, nitrogen, krypton and xenon.
[0108] The embodiment of the present invention also provides a battery. Figure 2 It is a schematic diagram of the discharge state of the battery provided by the embodiment of the present application, as Figure 2 shown, the battery includes a housing and an electrode assembly. The electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3. The separator 3 is disposed between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly may be a stacked structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2 in sequence. In some other embodiments, the electrode assembly may also be a wound structure, which is formed by winding the positive electrode sheet, the separator and the negative electrode sheet in sequence after stacking.
[0109] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 101 and a positive electrode active layer 102 disposed on at least one surface of the positive electrode current collector 101.
[0110] In some embodiments, the positive electrode current collector 101 may use aluminum foil or nickel foil, etc., and may also be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active layer 102 contains a positive electrode active material, and the positive electrode active material includes a compound that can reversibly intercalate and deintercalate metal ions.
[0111] In some embodiments, the positive electrode active material includes at least one of sodium transition metal oxides, polyanion-type compounds and Prussian blue compounds. Among the sodium transition metal oxides, the transition metal may be one or several of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The sodium transition metal oxide is, for example, Na x MO 2 , where M is one or several of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0 < x ≤ 1. The polyanion-type compound includes sodium vanadium trifluorophosphate Na 3 V 2 (PO 4 ) 2 F 3 , sodium fluorophosphate vanadate NaVPO 4 F, sodium vanadium phosphate Na 3 V 2 (PO 4 ) 3 、Na4 Fe 3 (PO 4 ) 2 P 2 O 7 、NaFePO 4 、Na 3 V 2 (PO 4 ) 3 Prussian blue compounds are NaxM 1 M 2 (CN) 6 , where M 1 、M 2 It is one or more of Fe, Mn, Co, Ni, Cu, Zn, Cr, Ti, V, Zr, and Ce, wherein 0<x≤2.
[0112] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 201 and a negative electrode active material layer 202 disposed on at least one surface of the negative electrode current collector.
[0113] In some embodiments, the negative electrode current collector 201 may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer 202 includes a negative electrode material, which is the negative electrode material of the first aspect described above or the negative electrode material prepared by the above preparation method.
[0114] The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.
[0115] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.
[0116] Example 1
[0117] (1) 1 kg of phenolic resin and 10 g of carbon nanotubes containing amino groups were mixed, and mixed in a VC machine at 400 r for 60 min. The obtained mixture was subjected to low-temperature heat treatment at 80° C. in a nitrogen atmosphere for 8 h to obtain a cross-linked and cured precursor. The precursor was crushed by a jaw crusher and a double-roll crusher, and then treated by a gas powder mill to make the volume median particle size of the precursor D50 = 5 μm;
[0118] (2) The precursor is placed in a low-pressure reactor and pumped to a pressure of 0.01 Pa by a mechanical pump and a molecular pump; the plasma glow discharge power is set to 400 W. After ignition, hydrogen is introduced to perform the first stage modification treatment on the surface of the precursor at 25°C for 20 minutes. The reactor is then heated to 700°C, and the precursor is subjected to the second stage modification treatment by plasma for 120 minutes. The glow discharge device is then turned off and the mixture is naturally cooled to room temperature to obtain a composite.
[0119] (3) The composite was sintered at 1200°C in a nitrogen atmosphere for 3 h and then naturally cooled to obtain the negative electrode material.
[0120] According to the preparation process of Example 1, Examples 2 to 16 and Comparative Examples 1 to 5 were prepared. The differences in process parameters of each Example and Comparative Example are shown in Table 1:
[0121] Table 1. Process parameters
[0122]
[0123]
[0124] Test Method
[0125] 1) The particle size distribution range of the negative electrode material is tested by Malvern laser particle size analyzer (Mastersizer 3000), and the volume-based cumulative particle size distribution of the particle size distribution is measured by laser diffraction method. D10 represents the particle size corresponding to when the cumulative particle size distribution percentage of the powder reaches 10%, D50 represents the particle size corresponding to when the cumulative particle size distribution percentage reaches 50%, and D90 represents the particle size corresponding to when the cumulative particle size distribution percentage reaches 90%, so that the particle size distribution of the negative electrode material (D 90 -D 10 ) / D 50 .
[0126] 2) The specific surface area of the negative electrode material was tested using a Micromeritics Tristar II 3030 specific surface area and pore size analyzer. A certain mass of powder was weighed and completely degassed under vacuum heating to remove the surface adsorbate. The specific surface area of the particles was calculated using the nitrogen adsorption method based on the amount of nitrogen adsorbed.
[0127] 3) SEM test: The surface morphology of the material was tested by Hitachi S4800 scanning electron microscope.
[0128] 4) Dry the material sample at 120°C for 2 hours, take 1±0.05g of the sample and burn it in a muffle furnace at 900°C for 3 hours in an air atmosphere, weigh it after cooling, and calculate the weight loss rate to obtain the ash content of the material;
[0129] 5) Testing method for the size of carbon nanotubes: The average length of carbon nanotubes was measured using atomic force microscopy (AFM) and high power transmission microscopy (HRTEM); the outer diameter of carbon nanotubes was measured in accordance with the national standard of the People's Republic of China GB / T 26826-2011.
[0130] 6) Test method for powder conductivity:
[0131] The powder conductivity performance of the material was tested using the MCP-PD51 powder conductivity meter produced by Mitsubishi Chemical of Japan and the four-probe method powder conductivity tester. 2.5 grams of carbon material was taken, and the volume and density of the powder after being compacted under a pressure of 20kN were tested. A certain voltage was applied to calculate the powder conductivity of the material.
[0132] 7) Testing method of compaction density:
[0133] Using the American CARVER 4350.22 powder compaction density tester, a sample of specified mass m is placed in a mold and a pressure of 5.0T is applied. After maintaining the pressure for 30s, the pressure is removed to test its thickness and the compaction density is calculated.
[0134] 8) The Raman spectrum of the carbon material was measured by a Raman spectrometer (trade name: Renishaw in Via, laser wavelength of 532 nm, manufactured by Renishaw Ltd., UK), and the carbon material was measured at 1350 cm -1 The peak intensity ID at 1580 cm -1 The ratio of the peak intensity IG at ID / IG, during the test, the carbon nanotube position and the carbon matrix position were selected for testing;
[0135] d002 is calculated by the Bragg equation 2dsinθ=nλ, where λ is the wavelength of the X-ray. The diffraction order n is any positive integer.
[0136] 9) Metal element content: Weigh 0.4-0.5 g sample, add 9 mL hydrochloric acid and 3 mL nitric acid, heat on a graphite digester for about 30 minutes to completely digest the trace elements in the sample, filter and fix the volume, and use inductively coupled plasma optical emission spectrometer (ICP-OES) to detect the content of trace elements.
[0137] 10) Electrochemical performance test: The electrochemical performance of the prepared negative electrode material was evaluated using a button half-cell. The specific method is as follows: The negative electrode material, conductive carbon black and LA133 binder prepared in the embodiment and the comparative example were weighed in a mass ratio of 91:3:6, and a high-speed disperser was used to adjust the viscous slurry to 45% solid content. The slurry was evenly coated on the copper foil with a scraper, and after drying in an oven at 80°C, the slurry was rolled and cut into a negative electrode sheet with a diameter of 14 mm. A sodium sheet with a diameter of 16 mm was used as the negative electrode sheet, a glass fiber with a model of GF / D from Whateman Company was used as the diaphragm, and a NaPF with a concentration of 1 mol / L was used. 6 A carbonate solution (diethyl carbonate DEC / ethylene carbonate EC volume ratio of 1:1) was used as the electrolyte and assembled in an argon-filled glove box to obtain a sodium ion button half-cell.
[0138] The results of the above performance tests are as follows:
[0139] Table 2. Performance test results of negative electrode materials
[0140]
[0141]
[0142] Table 3. Summary of electrochemical performance data
[0143]
[0144]
[0145] It can be seen from Tables 1 to 3 that according to the test data of Example 1, the compaction density of the negative electrode material is controlled at 1.3 g / cm 3 As mentioned above, the negative electrode material has a high compaction density, which can improve the energy density of the negative electrode material and the first coulombic efficiency of the negative electrode material. The slope area capacity of the negative electrode material can reach 150 mAh / g. In the present application, the negative electrode material can have high sodium storage capacity, high first efficiency and excellent electrochemical performance.
[0146] According to the test data of Examples 1 to 3, different resin-based carbon source materials and carbon nanotubes with different functional groups have little effect on the prepared negative electrode materials, and the negative electrode materials can all have high sodium storage capacity, high initial efficiency and excellent rate performance.
[0147] According to the test data of Example 1, Examples 4 to 7, and Comparative Example 2, as the mass ratio of carbon nanotubes to resin increases, and as more carbon nanotubes are added, the powder conductivity of the negative electrode material is significantly improved. This is because during the curing process, the carbon nanotubes can quickly cross-link with the resin with the assistance of amino groups and enter the resin matrix, interspersed inside the resin matrix, forming a highly interconnected three-dimensional network structure. Since carbon nanotubes have excellent conductive properties, only a small amount of carbon nanotubes need to be added. The conductivity of the negative electrode material of Example 1 is nearly ten times higher than that of the resin-based hard carbon negative electrode material provided in Comparative Example 2 without the addition of carbon nanotubes. Since the carbon nanotubes form a self-supporting effect inside the resin-based hard carbon, according to the XRD test data of the negative electrode material, the interlayer spacing d002 of the negative electrode material of Example 1 is It is larger than the interlayer spacing of traditional graphite and much larger than the interlayer spacing d002 of the negative electrode material prepared by the resin without adding carbon nanotubes. This is because the negative electrode material prepared in Example 1 has a self-supporting carbon nanotube-doped interconnected three-dimensional network structure, which can effectively expand the interlayer spacing, which is not only conducive to the insertion / extraction of sodium ions and increase its storage capacity, but also can maintain the stability of the negative electrode material during the charge and discharge cycle and high-rate charge and discharge process, so that the negative electrode material has excellent kinetic properties.
[0148] According to the Raman spectrum test of the negative electrode material, it was found that the doping of carbon nanotubes will not have a great impact on the degree of defects in the carbon matrix itself formed by the carbonization of the resin base. However, due to the addition of carbon nanotubes, trace elements in the negative electrode material, such as Fe and Ni, also increase. This is because the carbon nanotubes will carry a portion of Fe and Ni metals. According to the test data of Example 1, Example 8 to Example 10 and Comparative Example 4, it can be seen that as the temperature of the heat treatment increases, the time required for the heat treatment is shortened, and the heat treatment temperature is within a suitable range. The prepared negative electrode material can have high sodium storage capacity, high initial efficiency and excellent electrochemical properties. During the preparation process of Comparative Example 4, when the heat treatment temperature is too high, it will cause the functional group -NH 2 When the reaction with the -C=O group in the resin is terminated prematurely, that is, when the resin-based carbon source material is not completely cross-linked, the precursor is carbonized prematurely due to the excessively high heat treatment temperature, and a dense skeleton cannot be formed, resulting in a decrease in the compaction density and rate performance of the negative electrode material.
[0149] According to the test data of Example 1 and Example 11 to Example 14, a large amount of plasma is generated under the action of reducing gas during the modification process. In the first stage of the modification process, the plasma washes the precursor material, greatly reducing the content of calcium and magnesium ions in the material. The content of calcium and magnesium ions in the negative electrode material of Example 13 is significantly higher than that in the negative electrode materials of Example 1 and Example 14. In the second stage of the subsequent modification process, as shown in the data of Example 1, Example 11 and Example 12, with the increase of temperature and glow discharge power, the plasma is given more energy, bombarding the surface of the precursor material, generating more defect structures, making the I of the carbon matrix measured by the Raman spectrum of the negative electrode material D / I G As the ratio increases, more defects are generated in the carbon matrix, which can effectively increase the sodium embedding capacity in the slope region above 0.1V. Plasma etching of amorphous carbon can also remove sp3 hybridized carbon in carbon nanotubes, increase the proportion of sp2 hybridized carbon in carbon nanotubes, and improve the I D / I G The ratio of is greatly reduced, which can effectively modify carbon nanotubes, so that the conductivity of carbon nanotubes can be further improved, and the conductivity of hard carbon materials has also been improved. As the plasma continuously etches the metal impurities in the negative electrode material, the generated metal ions will also be discharged with the carrier gas, the content of metal ions such as iron and nickel in the negative electrode material will be greatly reduced, and the rate performance of the negative electrode material can also be improved.
[0150] According to the test data of Example 1 and Comparative Example 5, when the plasma is treated for a long time at a high temperature, since the plasma normally acts on sp3 hybridized carbon with higher priority than sp2 hybridized carbon, the long modification treatment time will cause the energized plasma to continuously bombard the hard carbon body and the carbon nanotubes embedded therein, resulting in the plasma also eliminating the sp2 hybridized carbon, and the carbon nanotube structure is damaged. The Raman spectrum of the negative electrode material is measured as I D / I G The ratio increases significantly, the compaction density and conductivity of the negative electrode material decrease significantly, the kinetic performance decreases, and the rate performance also declines greatly.
[0151] According to the test data of Example 1 and Examples 15 to 16, different reducing gas flows can complete the modification of carbon nanotubes at relatively low temperatures. The accelerated plasma gas flow collides frequently with the complex. Through a series of physical and chemical changes, the plasma collides and impacts the pollutant molecules on the surface of the complex to form small molecular volatiles, which are immediately removed from the surface of the carbon nanotubes with the high-flow gas, thereby effectively reducing the content of trace elements such as calcium and magnesium on the surface of the complex and improving the first-cycle coulomb efficiency of the negative electrode material.
[0152] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.
Claims
1. A negative electrode material, characterized in that: The negative electrode material includes a carbon matrix and carbon nanotubes, at least part of the carbon nanotubes are inserted into the interior of the carbon matrix to form a support structure; The compaction density of the negative electrode material under 5T pressure is ≥1.3g / cm 3 The powder conductivity of the negative electrode material under a pressure of 20KN is 9.0×10 3 S / m~4.0×10 4 S / m; The button-type battery assembled from the negative electrode material has a sodium embedding capacity of ≥150 mAh / g in the slope region of a voltage range above 0.1 V.
2. The negative electrode material according to claim 1, characterized in that The carbon nanotubes D / I G ≤0.5; and / or, I of the carbon matrix D / I G ≥1.
3.
3. The negative electrode material according to claim 1, characterized in that It meets at least one of the following characteristics: (1) The carbon nanotubes include at least one of oligo-walled carbon nanotubes, single-walled carbon nanotubes and multi-walled carbon nanotubes; (2) The outer diameter of the carbon nanotubes is 0.3 nm to 20 nm; (3) The average length of the carbon nanotubes is 10 nm to 10 μm; (4) Interlayer spacing of the carbon matrix 4. The negative electrode material according to claim 1, characterized in that It meets at least one of the following characteristics: (1) The volume median particle size D of the negative electrode material 50 3μm~30μm; (2) The particle size distribution index of the negative electrode material satisfies: 1.4≤(D 90 -D 10 ) / D 50 ≤1.6 (3) Based on the mass of the negative electrode material, the ash content of the negative electrode material is 0.005% to 0.05%; (4) Based on the mass of the negative electrode material, the mass content of calcium and / or magnesium in the negative electrode material is less than 6 ppm; (5) Based on the mass of the negative electrode material, the mass content of iron and / or nickel in the negative electrode material is less than 3 ppm.
5. The negative electrode material according to any one of claims 1 to 4, characterized in that: The button-type battery assembled from the negative electrode material has an initial coulombic efficiency of ≥93% and a reversible charge specific capacity of ≥360 mAh / g.
6. A method for preparing a negative electrode material, characterized in that: The method comprises the following steps: A mixture including a resin-based carbon source material and carbon nanotubes containing functional groups is heat-treated and crushed to obtain a precursor; wherein the functional groups include at least one of hydroxyl, carboxyl, ether, amino and metal ions; Using a plasma-treated reducing gas flow to modify the surface of the precursor to obtain a composite; The composite is carbonized to obtain a negative electrode material.
7. The preparation method according to claim 6, characterized in that: It meets at least one of the following characteristics: (1) The resin-based carbon source material includes at least one of a thermosetting resin and a thermoplastic resin; (2) The resin-based carbon source material includes at least one of epoxy resin, phenolic resin, polyvinyl chloride resin and polyurethane; (3) The mass ratio of the resin-based carbon source material to the carbon nanotubes containing functional groups is (10-10000):1; (4) The temperature of the heat treatment is 80°C to 200°C; (5) The heat treatment time is 10 min to 600 min; (6) Based on the mass of the precursor, the ash content of the precursor is ≤0.5%; (7) The heat treatment is carried out under a protective atmosphere, wherein the protective atmosphere comprises at least one of nitrogen, argon, helium, carbon monoxide, carbon dioxide, air and oxygen; (8) The carbon nanotubes containing functional groups include at least one of oligo-walled carbon nanotubes, single-walled carbon nanotubes and multi-walled carbon nanotubes; (9) The volume median particle size D of the precursor 50 3μm~30μm.
8. The preparation method according to claim 6, characterized in that: It meets at least one of the following characteristics: (1) The reducing gas stream comprises a reducing gas, and the reducing gas comprises at least one of carbon monoxide, hydrogen, hydrogen sulfide, methane and sulfur monoxide; (2) The reducing gas flow further includes a carrier gas, and the carrier gas includes at least one of nitrogen, argon, helium, and carbon dioxide; (3) The reducing gas flow further includes a carrier gas and a reducing gas, and the volume ratio of the reducing gas to the carrier gas is 1:(1-100); (4) The modification treatment includes a first stage and a second stage. The temperature of the first stage is 20°C to 40°C, and the treatment time of the first stage is 10min to 120min. The temperature of the second stage is 700°C to 800°C, and the treatment time of the second stage is 10min to 300min.
9. The preparation method according to claim 6, characterized in that: It meets at least one of the following characteristics: (1) The temperature of the carbonization treatment is 1000° C. to 1400° C.; (2) The carbonization treatment time is 0.5h to 4h; (3) The carbonization treatment is carried out under a protective atmosphere, and the protective atmosphere includes at least one of helium, neon, argon, nitrogen, krypton and xenon.
10. A battery, characterized in that: The battery comprises the negative electrode material according to any one of claims 1 to 5 or the negative electrode material prepared by the method for preparing the negative electrode material according to any one of claims 6 to 9.
Citation Information
Cited By
Porous carbon particle and preparation method thereof, negative electrode active material and secondary battery
CN121282198A
